Measuring Impact, Uncovering Bias?: citation Analysis of Literature on Women in Terrorism - Davis, Jessica (Perspectives on terrorism, 2021)
This article examines the research literature on women and terrorism and tries to determine whether there is a lack of research on women and terrorism, and whether this research is well-integrated into the broader research literature in terrorism studies. Literature on women and terrorism was identified using citation chaining and Google Scholar. From there, we categorized this scholarship to evaluate the breadth of the subjects under study. We also counted the citations that each publication received. Our findings suggest that there is a tendency for the literature on women in terrorism to be well cited within the subfield, but that the topic is much less well referenced in other parts of the literature, and is thus poorly integrated into the broader terrorism literature.